The Effect of 8-week Aerobic Exercise with Purslane Supplementation Consumption on Peroxidant and Antioxidants Indicators in Women with Type 2 Diabetes - M Fakoori Jouibari; P Farzanegi; AR Barari (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2014)
Introduction: Influence of physical activity with supplement consumption on the decrease of free radicals effects is not well known during exercise. Purslane is one of the richest sources of omega-3 fatty acid. Thus, the purpose of this study was to investigate the effect of 8-week exercise with Purslane consumption on peroxidant and antioxidants indicators (MDA, SOD, CAT) in women with type 2 diabetes. Methods: 28 sedentary women with type 2 diabetes participated in this study with average age of 50 years and with no history of regular exercise that were randomly divided into 4 groups: control (C), exercise (E), supplementation (S) and exercise + supplementation (E+S). Training programs were 60-75 minutes of aerobic exercise, 3 times in week with 50-70% of maximal heart rate. S and E+S groups consumed 5gr of Purslane seeds with lunch and performed aerobic exercise after 3 hours. Also, 2/5 gr Purslane was consumed with dinner. Blood samples were taken in two phases (before and after 8 weeks) following 12 to 14 hours of being fasted. Results: MDA decreased significantly, but SOD and CAT levels increased significantly in E, S, E+S groups after 8 weeks (P> 0/05). Also there was a significant difference between MDA in E and E+S groups after 8 weeks (P=0/015). Conclusion: The results showed that regular aerobic exercise with Purslane consumption can improve peroxidant and antioxidant balance in women with type 2 diabetes and prevent exercise-induced oxidative stress and also diabetes.